Trade liberalization and poverty reduction - Devashish Mitra (IZA World of Labor, 2016)
Economic growth is essential, though not sufficient, for poverty reduction in developing countries. Research based on many different approaches and including both cross- country and intra-country studies shows that international trade can contribute to economic growth, and thus can help many poor people escape poverty. However, the domestic environment has to be conducive to realizing the poverty-reduction benefits of increased trade. Complementary domestic policies and institutions needed include regulations that foster labor mobility, adequate financial development, and good public infrastructure.
Keywords: F1; F6; O1; O5; 330; international trade; reforms; poverty reduction; growth; labor markets